A Study on Solid Waste Composition and Characteristics of Mosul City/Iraq - Al- Rawi, Sati M.; Al-Tayyar, Taha A. (Science Journal of University of Zakho, 2013)
Mosul city, like many other cities in IRAQ, is currently experiencing serious problems at all stages of solid-waste management, that is the collection, sorting, transportation, and disposal of garbage. Presently,  Mosul city (1.52 millions inhabitants and 3.0 % growth rate) produces over 377264 tons of waste a year or 1033.6 tons per day .The above estimates was obtained through  solid waste survey comprising selected  families. These families were thought to represent the city  in terms of cultural, religious, economical and social aspects. 1680 sample of solid waste were collected from February  to end of June 2009. The results revealed that the city generated 0.68 kg/capita/day and that the usual composition was dominated by organic and food constituents. It appeared that social & economical aspects as well as the current instability and insecurity conditions of the country had a considerable impacts on both generation and composition of solid waste. The average studied physical and chemical properties were estimated and tabulated. Their values were (65-480Kg/m3), (90812KJ/Kg ), (50.2%) and (48.86Kg/100Kg) for density, total energy, moisture content and dry weight  respectively.
Keywords: solid waste; composition; Waste Generation; solid waste characteristics